Mastering the audition : how to perform under pressure - Soto-Morettini, Donna (Methuen Drama, 2012)
"Frustrating, nerve-wracking, job-winning or job-losing, flawed yet necessary--auditioning is a maddening business for everyone involved. The people behind the audition desk are looking for a killer audition, but most of the auditionees walk into the room feeling nervous, unprepared, and unable to control their own performance. Drawing on some fascinating, cutting-edge research into how the brain copes and responds in high-stress situations, 'Mastering the Audition' looks closely at the effects of fear, at our flawed ability to assess or 'really' know ourselves, at what drives us, and at what it takes to master the audition experience"--Publisher's description on back cover.